KESIAPAN MAHASISWA MANAJEMEN MENGHADAPI TANTANGAN TRANSFORMASI DIGITAL BERBASIS ARTIFICIAL INTELLIGENCE (AI). (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
he increasingly rapid digital transformation has driven major changes in the world of management, especially with the presence of Artificial Intelligence (AI) technology which is increasingly widely used in business decision-making processes. This study aims to analyze the level of readiness of management students in facing the challenges of AI-based digital transformation, focusing on three main aspects: knowledge of AI, attitudes towards AI, and digital skills. The study was conducted using a descriptive quantitative approach to 20 active students of the Management Study Program at the Andi Sapada Institute. The instrument used was a Likert scale questionnaire 1–5 and was analyzed using descriptive statistics. The results of the study showed that students had fairly good knowledge of AI (average score 3.60) and a very positive attitude towards the technology (average 4.05). However, their practical digital skills were still relatively low (average 2.90). These findings indicate the need to improve students' technical competence through training, technology-based curriculum integration, and collaboration with industry. This study contributes to the development of digital readiness literature in higher education and is an important input for institutions in designing learning strategies that are adaptive to the AI-based industrial era.